2012
DOI: 10.1080/19440049.2012.714908
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring ofDinophysisspecies and diarrhetic shellfish toxins in Flødevigen Bay, Norway: inter-annual variability over a 25-year time-series

Abstract: The accumulation of phycotoxins in bivalve mussels associated with mussels feeding on toxic phytoplankton is a well-known phenomenon in Norway. Regular monitoring for 25 years has revealed that accumulation of Diarrhetic Shellfish poisoning (DSP) toxins in mussels is the main phycotoxin problem along the Norwegian coast. The aim of this study was to evaluate possible trends over time of Dinophysis spp. and DSP as well as possible correlation between abundance of Dinophysis spp. and toxin accumulation in mussel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 22 publications
2
13
1
Order By: Relevance
“…Similar shifts in the Dinophysis community were reported along the Norwegian and Sardinian coasts by Naustvoll et al. () and Bazzoni et al. (), respectively, through their analyses of 25‐year time‐series data sets.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Similar shifts in the Dinophysis community were reported along the Norwegian and Sardinian coasts by Naustvoll et al. () and Bazzoni et al. (), respectively, through their analyses of 25‐year time‐series data sets.…”
Section: Discussionsupporting
confidence: 84%
“…Naustvoll et al. () did not observe a relationship between nutrients and Dinophysis and hypothesized changes in the Dinophysis community may be influenced by shifts in the prey community it relies on. Additionally, dinoflagellate parasites, such as Amoebophrya and Parvilucifera , are known to infect and impact some Dinophysis populations (Park et al.…”
Section: Discussionmentioning
confidence: 99%
“…Belgrano et al (1999) linked abundance of D. acuta in the Skagerrak, western Sweden, to periods of positive values of the NAO, and suggested that large-scale climatic processes govern the interannual variability of D. acuta, ruling out the hypothesis of an increasing trend in recent decades. Naustvoll et al (2012) observed a decrease of D. acuta numbers on the southern Norwegian coast on the basis of a 25-year time series . Concerning Dinophysis spp.…”
Section: Interannual Climate Variability and Trends In Dinophysis Popmentioning
confidence: 93%
“…to environmental conditions, the lack of long-term time series data has hindered progress in understanding the factors controlling their interannual variability. Multidecadal climate oscillations have been proposed to explain long-term variations in Dinophysis blooms in the Skagerrak, in western Swedish (Belgrano et al, 1999) and southern Norwegian coastal waters (Edwards et al, 2006;Naustvoll et al, 2012). These authors suggested that long-term changes of Dinophysis blooms in these areas were related to phase changes of the North Atlantic Oscillation (NAO), the most important mode of low-frequency variability of atmospheric circulation in the northern hemisphere (Hurrell, 1995).…”
Section: Introductionmentioning
confidence: 97%
“…Therefore, these samples of oyster were still safe for human consume. However, long-term studies have also showed that the contamination of DSP toxins in shellfish at the same location may have significant year-to-year variation and even more significant between multiannual periods 21,32 . So the presence of OA and DTX-2 in oyster, even at very low levels, confirmed the potential risk of DSP outbreak in Vietnam and the necessity of monitoring toxins in shellfish for human consume in general.…”
Section: Discussionmentioning
confidence: 99%